Răspuns :
a + b = 16√3 ⇒ a = 16√3 - b
a² - b² = 80 ⇒ (16√3 - b)² - b² = 80 ⇒ 768 - 32√3b + b² - b² = 80
⇒ 32√3b = 768 - 80 ⇒ b = 688/32√3 = 43/2√3 = 43√3/6
⇒ a = 16√3 - b = 16√3 - 43√3/6 = (96√3 - 43√3)/6 = 53√3/6
a² - b² = 80 ⇒ (16√3 - b)² - b² = 80 ⇒ 768 - 32√3b + b² - b² = 80
⇒ 32√3b = 768 - 80 ⇒ b = 688/32√3 = 43/2√3 = 43√3/6
⇒ a = 16√3 - b = 16√3 - 43√3/6 = (96√3 - 43√3)/6 = 53√3/6
A+b=16√3
A²-b²=80
(a-b)(a+b)=80
A-b=5√3/3
A+b=16√3
2a=5√3/3+16√3
2a=5353√3/3
A=53√3/6
B=16√3-53√3/6=(96√3-53√3)/6=43√3/6
A=53√3/6
B=43√3/6
A²-b²=80
(a-b)(a+b)=80
A-b=5√3/3
A+b=16√3
2a=5√3/3+16√3
2a=5353√3/3
A=53√3/6
B=16√3-53√3/6=(96√3-53√3)/6=43√3/6
A=53√3/6
B=43√3/6